Pengaplikasian permodelan air tanah pada lingkungan pertambangan - satria fitrio; Tedy Agung Cahyadi; Barlian Dwinagara (Retii, 2020)
Simulations in open pit drainage/dewatering, flooding, and environmental impact assessments were carried out using groundwater flow models. In mining hydrogeology, the utility of numerical models is very limited because of the uncertainty associated with the assumptions of hydrogeological parameters and boundary conditions. Among them is a lack of data in identifying hydrogeological conditions, changes in rainfall and evaporation cycles, changes due to land management due to mining activities, changes in mining work schedules, and post-mining void flooding. Numerical modeling is a tool used in diagnosing, managing, and predicting water behavior in soil, which has become increasingly important in recent years. Although mathematical modeling has its advantages, mathematical modeling cannot be the source of all answers to all questions related to groundwater. Modelling is a dynamic tool that must always be developed for the continuous improvement process, to become a representation of natural phenomena. Thus, this review presents a methodological approach to find out the numerical model, overcoming its capabilities and limitations, in the case of different applications in the mining industry, such as open-pit drainage/dewatering and heap leach. Therefore, the purpose of this study through a literature review conducted is to determine how the application of groundwater modeling in an open-pit mining environment is based on the case study examples in this literature.